Error mitigation using RaptorQ codes in an experimental indoor free space optical link under the influence of turbulence. Issue 14 (1st September 2015) - Pernice, Riccardo; Parisi, Antonino; Andò, Andrea; Mangione, Stefano; Garbo, Giovanni; Busacca, Alessandro C.; Perez, Joaquin; Ghassemlooy, Zabih
Abstract : In free space optical (FSO) communications, several factors can strongly affect the link quality. Among them, one of the most important impairments that can degrade the FSO link quality and its reliability – even under the clear sky conditions – consists of optical turbulence. In this work, the authors investigate the generation of both weak and moderate turbulence regimes in an indoor environment to assess the FSO link quality. In particular, they show that, due to the presence of the turbulence, the link experiences both erasure errors and packet losses during transmission, and also compare the experimental statistical distribution of samples with the predicted Gamma–Gamma model. Furthermore, the authors demonstrate that the application of the RaptorQ codes noticeably improves the link quality decreasing the packet error rate (PER) by about an order of magnitude, also offering – in certain cases – an error‐free transmission with a PER of ∼10 −2 at Rytov variance value of 0.5. The results show that the recovery rate increases with the redundancy, the packet length and the number of source packets, and it decreases with increasing data rates.